Pengaruh Pengungkapan CSR, Likuiditas dan Pertumbuhan Penjualan terhadap Kinerja Keuangan Perusahaan - Najwa Putri Maharani; Aina Zahra Parinduri (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the effect of Corporate Social Responsibility (CSR) disclosure, liquidity, and sales growth on the financial performance of basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sample consists of 120 observations selected using purposive sampling. Secondary data were obtained from annual reports and financial statements. Panel data analysis was conducted using EViews, with outlier treatment applied to reduce bias from extreme values. The results indicate that CSR disclosure has no significant effect on financial performance, suggesting that CSR activities do not directly enhance short-term profitability. Liquidity has a negative effect on financial performance, indicating inefficient use of excess current assets. In contrast, sales growth has a positive and significant effect on financial performance, confirming that increased sales contribute to improved corporate profitability.